Cathode materials and batteries
By controlling the ratio Li/O of the lithium content to the oxygen content at the surface layer of the positive electrode material of the battery, the lithium-containing coating is used to increase the discharge voltage of the battery, and solving the problem of low battery discharge voltage in the prior art, achieving higher energy density and charge and discharge efficiency.
Patent Information
- Application Number
- CN202180024532.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-04-02
- Filing Date
- 2021-03-15
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2041-03-15
AI Technical Summary
In the prior art, the discharge voltage of the battery is low, making it difficult to meet the needs of high-efficiency batteries.
A coated active material consisting of a positive electrode active material and a coating layer is used, which contains oxygen and lithium, and the ratio Li/O of the lithium content to the oxygen content is 0.26 or less at the surface layer portion of the positive electrode material.
Through this technical means, the discharge voltage of the battery is significantly improved, and the energy density and charge and discharge efficiency of the battery are enhanced.
Smart Images

Figure CN115336047B_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to positive electrode materials and batteries. Background Art
[0002] Patent Document 1 discloses an all-solid-state battery using a positive electrode active material coated with a coating material.
[0003] Prior art literature
[0004] Patent Document 1: International Publication No. 2019 / 135322 Summary of the invention
[0005] In the prior art, it is hoped to further increase the discharge voltage of the battery.
[0006] The positive electrode material of one embodiment of the present disclosure comprises:
[0007] Positive electrode active material, and
[0008] a coating layer covering the positive electrode active material,
[0009] The coating layer contains oxygen and lithium,
[0010] The positive electrode active material and the coating layer constitute a coated active material.
[0011] In the surface layer portion of the coated active material, a ratio of lithium content to oxygen content, Li / O, is 0.26 or less in terms of atomic ratio.
[0012] According to the present disclosure, the discharge voltage of the battery can be increased. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 This is a cross-sectional view schematically showing the structure of the positive electrode material 1000 according to the first embodiment.
[0014] Figure 2 This is a cross-sectional view schematically showing the structure of a battery 2000 according to the second embodiment. DETAILED DESCRIPTION
[0015] (Overview of one aspect of the present disclosure)
[0016] The positive electrode material of the first aspect of the present disclosure comprises:
[0017] Positive electrode active material, and
[0018] a coating layer covering the positive electrode active material,
[0019] The coating layer contains oxygen and lithium,
[0020] The positive electrode active material and the coating layer constitute a coated active material.
[0021] In the surface layer portion of the coated active material, a ratio of lithium content to oxygen content, Li / O, is 0.26 or less in terms of atomic ratio.
[0022] According to the first aspect, the discharge voltage of the battery can be increased.
[0023] According to a second aspect of the present disclosure, for example, in the positive electrode material of the first aspect, the coating layer may contain an alkali metal salt. According to the second aspect, the potential stability of the coating layer is improved, and the discharge voltage of the battery can be increased.
[0024] According to a third aspect of the present disclosure, for example, a solid electrolyte may be further included in the positive electrode material of the first aspect or the second aspect. According to the third aspect, the ion conductivity of the positive electrode can be improved.
[0025] In the fourth embodiment of the present disclosure, for example, in the positive electrode material of the third embodiment, the solid electrolyte may be composed of a composition formula Li α M β X γ In other words, α, β and γ can each independently be a value greater than 0, M can contain at least one element selected from metal elements and metalloid elements other than Li, and X can contain at least one element selected from F, Cl, Br and I. According to the fourth embodiment, the output density of the battery can be increased. In addition, the thermal stability of the battery can be improved, and the generation of harmful gases such as hydrogen sulfide can be suppressed.
[0026] According to a fifth aspect of the present disclosure, for example, in the positive electrode material of the fourth aspect, M may contain yttrium.
[0027] According to a sixth aspect of the present disclosure, for example, in the positive electrode material of the fourth aspect or the fifth aspect, 2.5≤α≤3, 1≤β≤1.1, and γ=6 may be satisfied.
[0028] According to a seventh aspect of the present disclosure, for example, in the positive electrode material according to any one of the fourth to sixth aspects, X may contain at least one selected from Cl and Br.
[0029] According to the fifth to seventh aspects, the ion conductivity of the solid electrolyte can be further improved, thereby improving the output density of the battery.
[0030] According to an eighth aspect of the present disclosure, in the positive electrode material according to any one of the first to seventh aspects, the coating layer may contain a lithium niobate compound. According to the eighth aspect, the charge and discharge efficiency of the battery can be further improved.
[0031] According to a ninth aspect of the present disclosure, in the positive electrode material of any one of the first to eighth aspects, the positive electrode active material may contain Li and at least one element selected from the group consisting of Mn, Co, Ni and Al. According to the ninth aspect, the energy density of the battery can be further improved.
[0032] A battery according to a tenth aspect of the present disclosure comprises:
[0033] A positive electrode comprising the positive electrode material according to any one of the first to ninth aspects,
[0034] Negative electrode, and
[0035] An electrolyte layer is disposed between the positive electrode and the negative electrode.
[0036] According to the tenth aspect, the discharge voltage of the battery can be increased.
[0037] According to the 11th aspect of the present disclosure, for example, in the battery of the 10th aspect, the electrolyte layer may include a solid electrolyte having the same composition as that of the solid electrolyte contained in the positive electrode material. According to the 11th aspect, the charge and discharge efficiency of the battery can be further improved.
[0038] According to the twelfth aspect of the present disclosure, for example, in the battery of the tenth or eleventh aspect, the electrolyte layer may include a halide solid electrolyte having a composition different from that of the solid electrolyte contained in the positive electrode material. According to the twelfth aspect, the output density and charge / discharge efficiency of the battery can be improved.
[0039] According to the 13th aspect of the present disclosure, for example, in the battery of any one of the 10th to 12th aspects, the electrolyte layer may include a sulfide solid electrolyte. According to the 13th aspect, a low potential negative electrode material such as graphite or metallic lithium can be used, and the energy density of the battery can be increased.
[0040] Hereinafter, embodiments of the present disclosure will be described with reference to the drawings.
[0041] (Implementation Method 1)
[0042] Figure 1 This is a cross-sectional view schematically showing the structure of the positive electrode material 1000 according to the first embodiment.
[0043] The positive electrode material 1000 of the first embodiment includes a coated active material 130 and a solid electrolyte 100 .
[0044] The coated active material 130 includes a positive electrode active material 110 and a coating layer 120. The coating layer 120 is provided on the surface of the positive electrode active material 110. The coating layer 120 is a layer containing a coating material. The positive electrode active material 110 is coated with the coating material. The coating layer 120 contains oxygen and lithium.
[0045] In the surface portion of the coated active material 130, the ratio of lithium content to oxygen content, Li / O, is less than 0.26 in terms of atomic ratio. The "surface portion of the coated active material 130" refers to the portion from the outermost surface of the coated active material 130 to a predetermined depth position. The "predetermined depth position" may be the position of composition information obtained using a surface composition analysis method. For example, when the thickness of the coating layer 120 exceeds the penetration depth of the soft X-ray or electron beam used in the composition analysis, the coating layer 120 is regarded as the "surface portion of the coated active material 130". When the thickness of the coating layer 120 is less than the penetration depth of the soft X-ray or electron beam used in the composition analysis, a portion of the positive electrode active material 110 and the coating layer 120 are included in the "surface portion of the coated active material 130".
[0046] The positive electrode active material 110 is separated from the solid electrolyte 100 by the coating layer 120. The positive electrode active material 110 may not be in direct contact with the solid electrolyte 100 because the coating layer 120 has ion conductivity.
[0047] According to the above structure, the discharge voltage of the battery can be increased.
[0048] Patent Document 1 mentions that during charging, an oxidative decomposition side reaction occurs in which electrons are extracted from a solid electrolyte in contact with the positive electrode active material. Along with this, an oxide layer lacking lithium ion conductivity is formed between the positive electrode active material and the solid electrolyte, and the interface resistance increases. In addition, it is mentioned that the formation of an oxide layer can be suppressed by providing a coating layer between the positive electrode active material and the solid electrolyte, thereby suppressing the increase in interface resistance. However, the surface composition of the coating layer is still unclear.
[0049] On the other hand, the inventors have made a concentrated study and found the following problem: if the battery is operated, the surface composition of the coated active material including the coating layer and the positive electrode active material changes, the interface resistance increases, and the discharge voltage decreases. As a result of further detailed investigation, the inventors found that the discharge voltage is improved by intentionally reducing the ratio of lithium content to oxygen content (Li / O) in the surface of the coated active material.
[0050] The coating layer 120 may contain an alkali metal salt as a coating material. The alkali metal salt may be a lithium salt. If the ratio (Li / O) of the surface layer of the coated active material 130 is reduced, the lithium of the alkali metal salt (e.g., lithium carbonate, lithium bicarbonate, lithium oxide, lithium hydroxide) contained in the coating layer 120 is reduced. If the lithium is reduced, the potential stability of the coating layer 120 is improved. If the potential stability of the coating layer 120 is improved, the formation of the oxide layer between the coated active material 130 and the solid electrolyte 100 is further suppressed, and the interface resistance of the electrode reaction is reduced. As a result, the discharge voltage of the battery can be increased.
[0051] The effect of improving the potential stability of the coating layer 120 is expected to suppress not only the formation of an oxide layer of the solid electrolyte but also the oxidation of the electrolyte solution. Therefore, the technology disclosed in the present invention is considered to be effective also in a battery containing an electrolyte solution.
[0052] The lithium salt may be contained in the coating layer as a by-product.
[0053] The method for controlling the ratio (Li / O) is not particularly limited. For example, a method of heat-treating the coated active material 130 in an oxygen atmosphere and recovering the coated active material 130 in an atmosphere with a dew point below -30°C after the heat treatment can be cited. The oxygen atmosphere can be a pure oxygen atmosphere. The heat treatment conditions and the atmospheric conditions when the coated active material 130 is removed from the heat treatment device after the heat treatment can be appropriately selected based on the composition of the positive electrode active material 110 and the coating layer 120.
[0054] As an analysis method for the surface composition of the coated active material 130, X-ray photoelectron spectroscopy (XPS), electron energy loss spectroscopy (EELS), etc. can be used. The analysis method of the surface composition is appropriately selected according to the composition of the coating material contained in the coating layer 120 and the coating state of the positive electrode active material 110. The surface composition analysis using XPS is not easy to be a local analysis, and a relatively wide area of the material surface can be evaluated. In addition, since the average surface composition information of 10nm from the deepest surface can be obtained, and the quality of the material is easy to manage, XPS is suitable as an analysis method for the surface composition.
[0055] The ratio (Li / O) may be greater than 0.01 and less than 0.26. When the ratio (Li / O) is greater than 0.01, the Li in the alkali metal salt is fully ensured. Therefore, the reduction in Li ion conductivity can be suppressed, thereby suppressing the increase in the internal resistance of the positive electrode material 1000. By suppressing the increase in the internal resistance of the positive electrode material 1000, the battery can operate at high output. The ratio (Li / O) may be greater than 0.13 and less than 0.26. If the ratio (Li / O) falls within such a range, the increase in interface resistance caused by the electrode reaction can be suppressed, and the coating layer 120 can be given high Li ion conductivity. As a result, the discharge voltage of the battery is further improved.
[0056] As the solid electrolyte 100 , a halide solid electrolyte can be used.
[0057] The halide solid electrolyte is represented by, for example, the following composition formula (1). In the composition formula (1), α, β, and γ are each independently a value greater than 0. M contains at least one element selected from metal elements and metalloid elements other than Li. X contains at least one element selected from F, Cl, Br, and I.
[0058] Li α M β X γ Formula (1)
[0059] Metalloid elements include B, Si, Ge, As, Sb, and Te. Metal elements include all elements included in Groups 1 to 12 of the periodic table except hydrogen, and all elements included in Groups 13 to 16 except B, Si, Ge, As, Sb, Te, C, N, P, O, S, and Se. That is, metal elements are a group of elements that can become cations when forming halogen compounds and inorganic compounds.
[0060] As the halide solid electrolyte, Li3YX6, Li2MgX4, Li2FeX4, Li(Al,Ga,In)X4, Li3(Al,Ga,In)X6, etc. can be used.
[0061] According to the above structure, the output density of the battery can be increased. In addition, the thermal stability of the battery can be improved, and the generation of harmful gases such as hydrogen sulfide can be suppressed.
[0062] In the present disclosure, when an element in a formula is expressed as "(Al, Ga, In)", this expression method represents at least one element selected from the element group in the brackets. That is, "(Al, Ga, In)" has the same meaning as "at least one selected from Al, Ga and In". The same is true for other elements. The halide solid electrolyte exhibits excellent ion conductivity. Furthermore, the halide solid electrolyte may not contain sulfur.
[0063] In the composition formula (1), M may contain Y (=yttrium). That is, the solid electrolyte 100 may contain Y as a metal element.
[0064] The composition formula (1) may satisfy 2.5≤α≤3, 1≤β≤1.1, and γ=6.
[0065] In the composition formula (1), X may contain at least one selected from Cl and Br.
[0066] According to the above structure, the ion conductivity of the solid electrolyte 100 can be further improved. As a result, the output density of the battery is improved.
[0067] The Y-containing halide solid electrolyte may be a compound represented by the following composition formula (2).
[0068] Li a M b Y c X6 formula (2)
[0069] The composition formula (2) satisfies a+mb+3c=6 and c>0. In the composition formula (2), M contains at least one element selected from metal elements and metalloid elements other than Li and Y. m is the valence of M. X contains at least one element selected from F, Cl, Br and I. M contains at least one element selected from Mg, Ca, Sr, Ba, Zn, Sc, Al, Ga, Bi, Zr, Hf, Ti, Sn, Ta and Nb. As the Y-containing halogenated solid electrolyte, specifically, Li3YF6, Li3YCl6, Li3YBr6, Li3YI6, Li3YBrCl5, Li3YBr3Cl3, Li3YBr5Cl, Li3YBr5I, Li3YBr3I3, Li3YBrI5, Li3YClI5, Li3YCl3I3, Li3YCl5I, Li3YBr2Cl2I2, Li3YBrCl4I, Li 2.7 Y 1.1 Cl6、Li 2.5 Y 0.5 Zr 0.5 Cl6、Li 2.5 Y 0.3 Zr 0.7 Cl6 etc.
[0070] According to the above structure, the output density of the battery can be further improved.
[0071] The solid electrolyte 100 may include a sulfide solid electrolyte.
[0072] As sulfide solid electrolytes, Li2S-P2S5, Li2S-SiS2, Li2S-B2S3, Li2S-GeS2, Li 3.25 Ge 0.25 P 0.75 S4, Li 10 GeP2S 12 etc. LiX, Li2O, MO can be added to it q , Li p MO q etc. Here, the element X in "LiX" is at least one element selected from F, Cl, Br and I. "MO q ” and “Li p MO q The element M in "MO" is at least one element selected from P, Si, Ge, B, Al, Ga, In, Fe and Zn. q ” and “Li p MO q "In this equation, p and q are independent natural numbers.
[0073] According to the above structure, the output density of the battery can be improved.
[0074] The solid electrolyte 100 may include at least one selected from an oxide solid electrolyte, a polymer solid electrolyte, and a complex hydride solid electrolyte.
[0075] As oxide solid electrolytes, for example, NASICON solid electrolytes represented by LiTi2(PO4)3 and its elemental substitution products, (LaLi)TiO3 perovskite solid electrolytes, and Li 14 ZnGe4O 16 , LISICON solid electrolytes represented by Li4SiO4, LiGeO4 and their elemental substitutions, Li7La3Zr2O 12 Garnet-type solid electrolytes represented by Li3N and its elemental substitutes, Li3PO4 and its N substitutes, glass or glass ceramics in which Li2SO4, Li2CO3 and other materials are added to a matrix containing Li-BO compounds such as LiBO2 and Li3BO3, etc.
[0076] As a polymer solid electrolyte, for example, a compound of a polymer compound and a lithium salt can be used. The polymer compound can have an ethylene oxide structure. By having an ethylene oxide structure, the polymer compound can contain a lot of lithium salts, so the ion conductivity can be further improved. As lithium salts, LiPF6, LiBF4, LiSbF6, LiAsF6, LiSO3CF3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9), LiC(SO2CF3)3, etc. can be used. As a lithium salt, one lithium salt selected from them can be used alone, or a mixture of two or more lithium salts selected from them can be used.
[0077] As the complex hydride solid electrolyte, for example, LiBH4-LiI, LiBH4-P2S5, etc. can be used.
[0078] According to the above structure, the output density of the battery can be improved.
[0079] As the positive electrode active material 110 of Embodiment 1, for example, lithium-containing transition metal oxides, transition metal fluorides, polyanion materials, fluorinated polyanion materials, transition metal sulfides, transition metal oxysulfide, transition metal oxynitride, etc. can be used. In particular, when lithium-containing transition metal oxides are used as the positive electrode active material 110, the manufacturing cost can be reduced and the average discharge voltage can be increased.
[0080] The positive electrode active material 110 may contain Li and at least one element selected from the group consisting of Mn, Co, Ni, and Al. Examples of such materials include Li(NiCoAl)O2, Li(NiCoMn)O2, and LiCoO2.
[0081] The positive electrode active material 110 may contain a single active material, or may contain a plurality of active materials having different compositions.
[0082] In Embodiment 1, the positive electrode active material 110 may be Li(NiCoMn)O 2 .
[0083] According to the above structure, the energy density of the battery can be further improved.
[0084] The positive electrode active material 110 has a particle shape, for example. The particle shape of the positive electrode active material 110 is not particularly limited. The particle shape of the positive electrode active material 110 may be spherical, ellipsoidal, scaly, or fibrous.
[0085] A material with low electron conductivity can be used as the coating material contained in the coating layer 120. As the coating material, an oxide material, an oxide solid electrolyte, an alkali metal salt, or the like can be used.
[0086] As oxide materials, for example, SiO2, Al2O3, TiO2, B2O3, Nb2O5, WO3, ZrO2, etc. can be used. As oxide solid electrolytes, for example, Li-Nb-O compounds such as LiNbO3, Li-BO compounds such as LiBO2 and Li3BO3, Li-Al-O compounds such as LiAlO2, Li-Si-O compounds such as Li4SiO4, Li-SO compounds such as Li2SO4, Li4Ti5O 12 Li-Ti-O compounds, Li-Zr-O compounds such as Li2ZrO3, Li-Mo-O compounds such as Li2MoO3, Li-VO compounds such as LiV2O5, Li-WO compounds such as Li2WO4, etc.
[0087] In Embodiment 1, the coating material may be an oxide solid electrolyte.
[0088] Oxide solid electrolytes have high ion conductivity and high potential stability. Therefore, by using oxide solid electrolytes, the charge and discharge efficiency of the battery can be further improved.
[0089] In Embodiment 1, the coating layer 120 may contain a lithium niobate compound as a coating material. The coating material may be LiNbO 3. The lithium niobate compound is a compound containing lithium, niobium, and oxygen.
[0090] LiNbO3 has higher ion conductivity and higher potential stability. Therefore, by using LiNbO3, the charge and discharge efficiency of the battery can be further improved.
[0091] In Embodiment 1, the coating material may be an alkali metal salt.
[0092] Since the electronic conductivity of the alkali metal salt is low, it is possible to suppress the degradation of the contact interface between the active material and the solid electrolyte. As the alkali metal salt, for example, lithium carbonate, lithium bicarbonate, lithium oxide, lithium hydroxide, etc. can be used. One alkali metal salt can be used alone, or a mixture of two or more alkali metal salts can be used.
[0093] The coating layer 120 may include a mixture of a coating material other than an alkali metal salt and an alkali metal salt. When the mixture is used for the coating layer 120, an effect of suppressing an increase in interface resistance can be obtained, and the ion conductivity of the coating layer 120 can be more easily controlled. As a result, the configuration of the positive electrode material 1000 can be designed in a wider range.
[0094] The thickness of the coating layer 120 may be greater than or equal to 1 nm and less than or equal to 100 nm.
[0095] When the thickness of the coating layer 120 is 1 nm or more, direct contact between the positive electrode active material 110 and the solid electrolyte 100 can be suppressed, and a side reaction of the solid electrolyte can be suppressed. Therefore, the charge and discharge efficiency can be improved.
[0096] Since the thickness of the coating layer 120 is 100 nm or less, the thickness of the coating layer 120 does not become too thick. Therefore, the internal resistance of the battery can be sufficiently reduced. As a result, the energy density of the battery can be increased. The thickness of the coating layer 120 can be determined by thinning the coated active material 130 using a method such as ion milling and observing the cross section of the coated active material 130 using a transmission electron microscope.
[0097] The coating layer 120 can similarly coat the particles of the positive electrode active material 110. This can suppress direct contact between the particles of the positive electrode active material 110 and the particles of the solid electrolyte 100, thereby suppressing side reactions of the solid electrolyte 100. Therefore, the charge and discharge efficiency can be improved.
[0098] Alternatively, the coating layer 120 may only cover a portion of the surface of the particles of the positive electrode active material 110. The particles of the plurality of positive electrode active materials 110 are in direct contact with each other via the portion without the coating layer 120, so that the electron conductivity between the particles of the positive electrode active material 110 is improved. Therefore, the battery can operate at a high output.
[0099] The shape of the solid electrolyte 100 of the first embodiment is not particularly limited, and may be, for example, needle-shaped, spherical, ellipsoidal, etc. For example, the shape of the solid electrolyte 100 may be granular.
[0100] For example, when the shape of the solid electrolyte 100 of the first embodiment is a particle (eg, a spherical shape), the median diameter may be 100 μm or less.
[0101] When the median diameter of the solid electrolyte 100 is 100 μm or less, the coated active material 130 and the solid electrolyte 100 can be well dispersed in the positive electrode material 1000. This improves the charge and discharge characteristics of the battery.
[0102] In the first embodiment, the median diameter of the solid electrolyte 100 may be 10 μm or less.
[0103] According to the above structure, the coated active material 130 and the solid electrolyte 100 can form a good dispersion state in the positive electrode material 1000 .
[0104] In the first embodiment, the median diameter of the solid electrolyte 100 may be smaller than the median diameter of the coated active material 130 .
[0105] According to the above structure, the solid electrolyte 100 and the coated active material 130 can be dispersed in the positive electrode material 1000 in a better manner.
[0106] The median diameter of the coated active material 130 may be greater than or equal to 0.1 μm and less than or equal to 100 μm.
[0107] When the median diameter of the coated active material 130 is 0.1 μm or more, the coated active material 130 and the solid electrolyte 100 can form a good dispersion state in the positive electrode material 1000. As a result, the charge and discharge characteristics of the battery are improved.
[0108] When the median diameter of the coated active material 130 is 100 μm or less, the lithium diffusion rate in the coated active material 130 is sufficiently ensured. Therefore, the battery can operate at a high output.
[0109] The median diameter of the coated active material 130 may be larger than the median diameter of the solid electrolyte 100. Thus, the coated active material 130 and the solid electrolyte 100 can be in a well-dispersed state.
[0110] In the positive electrode material 1000 of the first embodiment, the particles of the solid electrolyte 100 and the particles of the coated active material 130 may be as follows: Figure 1 At this time, the coating layer 120 and the positive electrode active material 110 are in contact with each other.
[0111] The positive electrode material 1000 of the first embodiment may include a plurality of particles of the solid electrolyte 100 and a plurality of particles of the coated active material 130 .
[0112] The content of the solid electrolyte 100 and the content of the coated active material 130 in the positive electrode material 1000 may be the same as or different from each other.
[0113] In this specification, the "median diameter" refers to the particle diameter when the cumulative volume in the volume-based particle size distribution is equal to 50%. The volume-based particle size distribution is measured, for example, by a laser diffraction measurement device or an image analysis device.
[0114] Next, a method for producing the positive electrode material 1000 will be described.
[0115] First, prepare the powder of the positive electrode active material 110. The powder of the positive electrode active material 110 is synthesized, for example, by a solid phase method. In the solid phase method, a plurality of raw material powders are mixed and fired to obtain the powder of the positive electrode active material 110. In addition, powders of the positive electrode active material 110 of various compositions are commercially available and easily available.
[0116] Next, the coating layer 120 is formed on the surface of the particles of the positive electrode active material 110. The method for forming the coating layer 120 is not particularly limited. Examples of the method for forming the coating layer 120 include a liquid phase coating method and a gas phase coating method.
[0117] For example, in the liquid phase coating method, a precursor solution of an ion conductive material is applied to the surface of the positive electrode active material 110. In the case of forming a coating layer 120 containing LiNbO3, the precursor solution may be a mixed solution (sol solution) of a solvent, lithium alcoholate, and niobium alcoholate. As lithium alcoholate, ethoxy lithium may be cited. As niobium alcoholate, ethoxy niobium may be cited. The solvent is, for example, an alcohol such as ethanol. The amounts of lithium alcoholate and niobium alcoholate are adjusted according to the target composition of the coating layer 120. Water may be added to the precursor solution as needed. The precursor solution may be acidic or alkaline.
[0118] The method of coating the precursor solution on the surface of the positive electrode active material 110 is not particularly limited. For example, the precursor solution can be coated on the surface of the positive electrode active material 110 using a tumble granulation coating device. By using the tumble granulation coating device, the precursor solution can be sprayed onto the positive electrode active material 110 while the positive electrode active material 110 is rolled and flowed, and the precursor solution is coated on the surface of the positive electrode active material 110. Thus, a precursor film is formed on the surface of the positive electrode active material 110. Then, the positive electrode active material 110 coated with the precursor film is heat-treated. The gelation of the precursor film is promoted by heat treatment to form a coating layer 120. Thus, a coated active material 130 is obtained. At this point in time, the coating layer 120 covers almost the entire surface of the positive electrode active material 110. The thickness of the coating layer 120 is roughly uniform.
[0119] As the gas phase coating method, there are pulsed laser deposition (PLD), vacuum evaporation, sputtering, thermal chemical vapor deposition (CVD), plasma chemical vapor deposition, etc. For example, in the PLD method, a high-energy pulse laser (for example, KrF excimer laser, wavelength: 248nm) is irradiated on an ion conductive material as a target material, so that the sublimated ion conductive material is deposited on the surface of the positive electrode active material 110. In the case of forming the coating layer 120 of LiNbO3, LiNbO3 sintered at a high density is used as the target material.
[0120] Next, the coated active material 130 is treated to adjust the ratio (Li / O). For example, the coated active material 130 is heat-treated in an oxygen atmosphere, and after the heat treatment, the coated active material 130 is recovered in an atmosphere with a dew point below -30°C. The oxygen atmosphere may be a pure oxygen atmosphere. The heat treatment conditions and the atmospheric conditions when the coated active material 130 is removed from the heat treatment device after the heat treatment may be appropriately selected based on the composition of the positive electrode active material 110 and the coating layer 120. The heat treatment temperature is, for example, above 150°C and below 1000°C. The heat treatment time is, for example, above 1 hour and below 72 hours. After the heat treatment, a treatment for re-crushing the coated active material 130 may be performed. For example, if the heat treatment temperature increases, the ratio (Li / O) tends to increase.
[0121] The pure oxygen atmosphere can be formed, for example, by the following method: That is, the inside of the chamber is replaced with oxygen with a purity of 99% or more, and the volume concentration of gases other than oxygen is reduced to less than 1%. The pressure of the pure oxygen atmosphere is, for example, equal to atmospheric pressure.
[0122] Through the above steps, the positive electrode material 1000 showing the desired ratio (Li / O) is obtained.
[0123] (Implementation Method 2)
[0124] Embodiment 2 will be described below. Explanations overlapping with those of Embodiment 1 described above will be appropriately omitted.
[0125] Figure 2 This is a cross-sectional view schematically showing the structure of a battery 2000 according to the second embodiment.
[0126] The battery 2000 according to the second embodiment includes a positive electrode 201 , an electrolyte layer 202 , and a negative electrode 203 .
[0127] The positive electrode 201 includes a positive electrode material 1000 .
[0128] The electrolyte layer 202 is disposed between the positive electrode 201 and the negative electrode 203 .
[0129] According to the above structure, the discharge voltage of the battery 2000 can be increased.
[0130] The volume ratio "v1:100-v1" of the coated active material 130 and the solid electrolyte 100 contained in the positive electrode 201 can satisfy 30≤v1≤95. When 30≤v1 is satisfied, the energy density of the battery 2000 is sufficiently ensured. In addition, when v1≤95 is satisfied, it is possible to operate at high output.
[0131] The thickness of the positive electrode 201 may be 10 μm or more and 500 μm or less. When the thickness of the positive electrode 201 is 10 μm or more, the energy density of the battery 2000 is sufficiently ensured. When the thickness of the positive electrode 201 is 500 μm or less, high-power operation is possible.
[0132] The electrolyte layer 202 is a layer containing an electrolyte. The electrolyte is, for example, a solid electrolyte. That is, the electrolyte layer 202 may be a solid electrolyte layer. As the solid electrolyte, the material exemplified in Embodiment 1 may be used. That is, the electrolyte layer 202 may contain a solid electrolyte having the same composition as the solid electrolyte contained in the positive electrode material 1000.
[0133] According to the above structure, the charge and discharge efficiency of the battery 2000 can be further improved.
[0134] Alternatively, the electrolyte layer 202 may include a halide solid electrolyte having a composition different from that of the solid electrolyte included in the positive electrode material 1000 .
[0135] According to the above structure, the output density and the charge and discharge efficiency of the battery 2000 can be improved.
[0136] The electrolyte layer 202 may include a sulfide solid electrolyte.
[0137] According to the above structure, since the sulfide solid electrolyte having excellent reduction stability is included, a negative electrode material having a low potential, such as graphite or metallic lithium, can be used, and the energy density of the battery 2000 can be increased.
[0138] As the sulfide solid electrolyte used for the electrolyte layer 202 , the sulfide solid electrolyte exemplified in Embodiment 1 can be used.
[0139] The electrolyte layer 202 may include at least one selected from an oxide solid electrolyte, a polymer solid electrolyte, and a complex hydride solid electrolyte. Examples of these materials are also as described in the first embodiment.
[0140] The electrolyte layer 202 may include only one solid electrolyte selected from the above solid electrolytes, or may include two or more solid electrolytes selected from the above solid electrolytes. The compositions of the multiple solid electrolytes are different from each other. For example, the electrolyte layer 202 may include a halide solid electrolyte and a sulfide solid electrolyte.
[0141] The thickness of the electrolyte layer 202 may be 1 μm or more and 300 μm or less. When the thickness of the electrolyte layer 202 is 1 μm or more, the positive electrode 201 and the negative electrode 203 are less likely to short-circuit. When the thickness of the electrolyte layer 202 is 300 μm or less, high-output operation is possible.
[0142] The negative electrode 203 includes a material having the property of storing and releasing metal ions (for example, lithium ions). The negative electrode 203 includes, for example, a negative electrode active material.
[0143] As the negative electrode active material, metal materials, carbon materials, oxides, nitrides, tin compounds, silicon compounds, etc. can be used. The metal material can be a single metal. Alternatively, the metal material can be an alloy. Examples of metal materials include lithium metal, lithium alloys, etc. Examples of carbon materials include natural graphite, coke, semi-graphitized carbon, carbon fiber, spherical carbon, artificial graphite, amorphous carbon, etc. From the viewpoint of capacity density, silicon (Si), tin (Sn), silicon compounds, and tin compounds can be preferably used.
[0144] The negative electrode 203 may include a solid electrolyte. According to the above structure, the lithium ion conductivity inside the negative electrode 203 can be improved, and high-power operation can be achieved. As the solid electrolyte, the materials exemplified in Embodiment 1 can be used.
[0145] The median diameter of the negative electrode active material can be greater than 0.1 μm and less than 100 μm. When the median diameter of the negative electrode active material is greater than 0.1 μm, the negative electrode active material and the solid electrolyte can form a good dispersion state in the negative electrode 203. As a result, the charge and discharge characteristics of the battery 2000 are improved. In addition, when the median diameter of the negative electrode active material is less than 100 μm, the diffusion rate of lithium in the negative electrode active material is fully ensured. Therefore, the battery 2000 can operate at high output.
[0146] The median diameter of the negative electrode active material may be larger than the median diameter of the solid electrolyte contained in the negative electrode 203. Thus, the negative electrode active material and the solid electrolyte can form a good dispersion state.
[0147] When the volume ratio of the negative electrode active material and the solid electrolyte of the negative electrode 203 is represented by "v2:100-v2", the volume ratio v2 of the negative electrode active material can satisfy 30≤v2≤95. When 30≤v2 is satisfied, the energy density of the battery 2000 is sufficiently ensured. In addition, when v2≤95 is satisfied, it is possible to operate at high output.
[0148] The thickness of the negative electrode 203 may be 10 μm or more and 500 μm or less. When the thickness of the negative electrode 203 is 10 μm or more, the energy density of the battery 2000 is sufficiently ensured. When the thickness of the negative electrode 203 is 500 μm or less, high-power operation is possible.
[0149] For the purpose of improving the adhesion of particles to each other, at least one of the positive electrode 201, the electrolyte layer 202 and the negative electrode 203 may include a binder. The binder is used to improve the adhesion of the material constituting the electrode. As a binder, polyvinylidene fluoride, polytetrafluoroethylene, polyethylene, polypropylene, aramid resin, polyamide, polyimide, polyamide-imide, polyacrylonitrile, polyacrylic acid, polymethyl acrylate, polyethyl acrylate, polyhexyl acrylate, polymethacrylic acid, polymethyl methacrylate, polyethyl methacrylate, polyhexyl methacrylate, polyvinyl acetate, polyvinyl pyrrolidone, polyether, polyether sulfone, hexafluoropolypropylene, styrene-butadiene rubber, carboxymethyl cellulose, etc. can be cited. In addition, as a binder, a copolymer of two or more materials selected from tetrafluoroethylene, hexafluoroethylene, hexafluoropropylene, perfluoroalkyl vinyl ether, vinylidene fluoride, trifluorochloroethylene, ethylene, propylene, pentafluoropropylene, fluoromethyl vinyl ether, acrylic acid, hexadiene can be used. In addition, two or more selected from them can be mixed and used as a binder.
[0150] For the purpose of improving electron conductivity, at least one of the positive electrode 201 and the negative electrode 203 may include a conductive additive. As the conductive additive, for example, graphite such as natural graphite or artificial graphite, carbon black such as acetylene black and Ketjen black, conductive fibers such as carbon fibers or metal fibers, metal powders such as carbon fluoride and aluminum, conductive whiskers such as zinc oxide or potassium titanate, conductive metal oxides such as titanium oxide, polyaniline, polypyrrole, and conductive polymer compounds such as polythiophene can be used. When a carbon conductive additive is used, the cost can be reduced.
[0151] The battery 2000 of the second embodiment can be configured as a battery in various shapes such as a coin type, a cylindrical type, a square type, a sheet type, a button type, a flat type, and a stacked type.
[0152] Example
[0153] Hereinafter, the details of the present disclosure will be described using Examples and Comparative Examples.
[0154] 《Example 1》
[0155] [Production of halide solid electrolyte]
[0156] In an argon glove box at a dew point of -60°C or less, LiCl powder, LiBr powder, and YCl3 powder were weighed in a molar ratio of LiCl:LiBr:YCl3=1:2:1. They were crushed and mixed in a mortar to obtain a mixture. Then, the mixture was ground at 600 rpm for 12 hours using a planetary ball mill.
[0157] As described above, powder of the halide solid electrolyte of Example 1 represented by the composition formula of Li3YBr2Cl4 was obtained.
[0158] [Preparation of coated active material]
[0159] Li(NiCoMn)O2 (hereinafter referred to as NCM) powder was vacuum dried at 100°C for 2 weeks. Then, the NCM powder was taken out from the drying device in a dry atmosphere with a dew point of -30°C or less.
[0160] Lithium ethoxide (manufactured by Kojun Chemical Co., Ltd.) and niobium pentaethoxide (manufactured by Kojun Chemical Co., Ltd.) were weighed in a molar ratio of 1:1 in an argon glove box at a dew point of -60°C or less, and dissolved in super dehydrated ethanol (manufactured by Wako Pure Chemical Industries, Ltd.) to prepare a coating solution.
[0161] When forming the coating layer on the surface of the dried NCM particles, a tumble flow granulation coating device (manufactured by POWREX, FD-MP-01E) was used.
[0162] The amount of NCM input, the stirring speed, and the feeding rate of the coating solution were 1 kg, 400 rpm, and 6.59 g / min, respectively. The amount of coating solution input was adjusted so that the film thickness of LiNbO3 was 6 nm. The amount of coating solution input was calculated using the specific surface area of the active material and the density of LiNbO3. A series of steps using a tumble granulation coating device were implemented in a dry atmosphere with a dew point below -30°C.
[0163] After the treatment for forming the coating layer was completed, the obtained powder was put into an alumina crucible and heat-treated at 350° C. for 1 hour in a pure oxygen atmosphere.
[0164] The heat-treated powder was taken out in a dry atmosphere with a dew point of -30°C or less and pulverized again using an agate mortar. Thus, the coated active material of Example 1 (NCM coated with a coating layer) was obtained.
[0165] The coating material contained in the coating layer is LiNbO3.
[0166] [Production of positive electrode materials]
[0167] The carbon conductive agent, the halide solid electrolyte of Example 1, and the coated active material of Example 1 were weighed in a weight ratio of 2:18:82 in an argon glove box at a dew point of -60°C or less. They were mixed in an agate mortar to prepare the positive electrode material of Example 1.
[0168] 《Example 2》
[0169] [Production of halide solid electrolyte]
[0170] The halide solid electrolyte (NCM) powder of Example 2 was obtained by the same method as Example 1.
[0171] [Preparation of coated active material]
[0172] The NCM powder was vacuum dried at 100°C for 2 weeks. Then, the NCM powder was heat treated at 400°C for 1 hour in a nitrogen atmosphere to dry the surface of the NCM particles. The NCM powder was taken out from the drying device in a dry atmosphere with a dew point of -30°C or less.
[0173] The coating layer was formed on the surface of the NCM particles in the same manner as in Example 1 except that the amount of coating solution added was adjusted so that the thickness of the LiNbO 3 film was 2 nm. Thus, the coated active material of Example 2 was obtained.
[0174] [Production of positive electrode materials]
[0175] The positive electrode material of Example 2 was obtained by the same method as Example 1 except that the coated active material of Example 2 was used.
[0176] 《Example 3》
[0177] The positive electrode material of Example 3 was obtained by the same method as in Example 2 except that the amount of coating solution added was adjusted so that the film thickness of LiNbO 3 was 6 nm.
[0178] 《Example 4》
[0179] A positive electrode material of Example 4 was obtained in the same manner as in Example 2 except that the amount of coating solution added was adjusted so that the film thickness of LiNbO 3 was 12 nm.
[0180] Comparative Example 1
[0181] [Production of halide solid electrolyte]
[0182] The halide solid electrolyte (NCM) powder of Comparative Example 1 was obtained by the same method as Example 1.
[0183] [Preparation of coated active material]
[0184] The NCM powder was vacuum dried at 100° C. for 2 weeks. Then, the NCM powder was taken out from the drying device in a dry atmosphere with a dew point of −30° C. or less.
[0185] Lithium ethoxide (manufactured by Kojun Chemical Co., Ltd.) and niobium pentaethoxide (manufactured by Kojun Chemical Co., Ltd.) were weighed to a molar ratio of 1:1 in an argon glove box at a dew point of -60°C or less, and dissolved in super dehydrated ethanol (manufactured by Wako Pure Chemical Industries, Ltd.) to prepare a coating solution.
[0186] When forming the coating layer on the surface of the dried NCM particles, a tumble flow granulation coating device (manufactured by POWREX, FD-MP-01E) was used.
[0187] The amount of NCM input, the stirring speed, and the feeding rate of the coating solution were 1 kg, 400 rpm, and 6.59 g / min, respectively. The amount of coating solution input was adjusted so that the film thickness of LiNbO3 was 2 nm. The amount of coating solution input was calculated using the specific surface area of the active material and the density of LiNbO3. A series of steps using a tumble granulation coating device were implemented in a dry atmosphere with a dew point below -30°C.
[0188] After the treatment for forming the coating layer was completed, the obtained powder was put into an alumina crucible and heat-treated at 350° C. for 1 hour in an air atmosphere.
[0189] The heat-treated powder was taken out in air atmosphere and pulverized again with an agate mortar. Thus, the coated active material of Comparative Example 1 was obtained.
[0190] The coating material contained in the coating layer is LiNbO3.
[0191] [Production of positive electrode materials]
[0192] The carbon conductive agent, the halide solid electrolyte of Comparative Example 1, and the coated active material of Comparative Example 1 were weighed at a weight ratio of 2:18:82 in an argon glove box at a dew point of -60°C or less. They were mixed in an agate mortar to prepare the positive electrode material of Comparative Example 1.
[0193] Comparative Example 2
[0194] A positive electrode material of Comparative Example 2 was obtained by the same method as Comparative Example 1 except that the amount of coating solution added was adjusted so that the film thickness of LiNbO 3 was 6 nm.
[0195] 《Comparative Example 3》
[0196] A positive electrode material of Comparative Example 3 was obtained by the same method as Comparative Example 1 except that the amount of coating solution added was adjusted so that the film thickness of LiNbO 3 was 12 nm.
[0197] [Production of sulfide solid electrolyte]
[0198] In an argon glove box with an Ar atmosphere at a dew point of -60°C, Li2S powder and P2S5 powder were weighed so that the molar ratio was Li2S:P2S5=75:25. Below. They were crushed and mixed in a mortar to obtain a mixture. Then, a planetary ball mill (manufactured by Fritsch, P-7 type) was used to grind the mixture for 10 hours at 510 rpm. Thus, a glassy solid electrolyte was obtained. The glassy solid electrolyte was heat treated at 270°C for 2 hours in an inert atmosphere. Thus, a glass-ceramic sulfide solid electrolyte was obtained.
[0199] [Manufacturing of Secondary Batteries]
[0200] Secondary batteries were prepared using the halide solid electrolyte of Example 1, the positive electrode materials of Examples 1 to 4 and Comparative Examples 1 to 3, and a sulfide solid electrolyte.
[0201] First, 80 mg of a sulfide solid electrolyte, 20 mg of a halide solid electrolyte, and 18 mg of a positive electrode material were stacked in this order in an insulating outer cylinder, and the resulting stack was press-molded at a pressure of 720 MPa to obtain a positive electrode and an electrolyte layer.
[0202] Next, metal In (thickness 200 μm), metal Li (thickness 300 μm) and metal In (thickness 200 μm) were sequentially stacked on the electrolyte layer on the side opposite to the side in contact with the positive electrode. The obtained stack was press-formed at a pressure of 80 MPa to produce a stack consisting of a positive electrode, an electrolyte layer and a negative electrode.
[0203] Next, stainless steel current collectors were placed above and below the stacked body, and current collecting leads were attached to each current collector.
[0204] Finally, the insulating outer cylinder was sealed with an insulating ferrule to isolate the interior of the outer cylinder from the external gas atmosphere, thereby producing batteries of Examples 1 to 4 and Comparative Examples 1 to 3.
[0205] [Charge and discharge test]
[0206] Using the batteries of Examples 1 to 4 and Comparative Examples 1 to 3, a charge and discharge test was carried out under the following conditions.
[0207] The battery was placed in a constant temperature chamber at 25°C.
[0208] Constant current charging was performed at a current value of 140 μA, which is a 0.05C rate (20 hour rate) relative to the theoretical capacity of the battery, and charging was terminated at a voltage of 3.7V.
[0209] Next, the battery was discharged at a current value of 140 μA, which was a 0.05 C rate, in the same manner, and the discharge was terminated at a voltage of 1.9 V.
[0210] As described above, the average discharge voltage of each of the batteries of Examples 1 to 4 and Comparative Examples 1 to 3 was measured. The results are shown in Table 1 below.
[0211] [Surface composition analysis]
[0212] The following measurements were performed using the coated active materials of Examples 1 to 4 and Comparative Examples 1 to 3.
[0213] The surface composition analysis by XPS was performed using QuanteraSXM (manufactured by ULVAC-PHI Co., Ltd.) The measurement conditions were as follows.
[0214] X-ray source: Al monochromatic (25W, 15kV)
[0215] Analysis area: 300μm×800μm (area)
[0216] Electron / ion neutralization gun: ON
[0217] Photoelectron extraction angle: 45 degrees
[0218] The scanning range of the binding energy is 0 eV to 1250 eV. The atomic concentration of the element is calculated using the software "MultiPak" manufactured by ULVAC-PHI.
[0219] As the elements to be measured, Li (scanning range: 45-65eV), C (scanning range: 275-295eV), O (scanning range: 522-542eV), Mn (scanning range: 632-662eV), Co (scanning range: 770-810eV), Ni (scanning range: 848-888eV), and Nb (scanning range: 195-215eV) were selected. The atomic concentration of the element was based on the peak observed in the scanning range of each element, and the surface concentration of each element was calculated based on the integrated peak area ratio. Then, the ratio (Li / O) was calculated as an atomic ratio from the calculated surface Li concentration and the calculated surface O concentration.
[0220] As described above, the atomic ratio (Li / O) of the lithium (Li) content to the oxygen (O) content in the region from the outermost surface of the coated active material to a depth of 10 nm was obtained. The results are shown in Table 1 below.
[0221] Table 1
[0222]
[0223] Investigation
[0224] As shown in Table 1, the coated active materials of Examples 1 to 4 have atomic ratios (Li / O) of 0.18, 0.26, 0.13, and 0.26, respectively. The coated active materials of Examples 1 to 4 all have an atomic ratio (Li / O) of 0.26 or less. The average discharge voltage of the batteries of Examples 1 to 4 is 3.624V or more. It was confirmed that the discharge voltage of the battery was improved by using a positive electrode material in which the atomic ratio (Li / O) of the lithium content to the oxygen content in the surface layer of the coated active material was 0.26 or less.
[0225] In contrast, the atomic ratios (Li / O) of the coated active materials of Comparative Examples 1 to 3 were 0.44, 0.34, and 0.33, which were significantly lower than those of Examples 1 to 4. The average discharge voltages of the batteries of Comparative Examples 1 to 3 were all 3.586 V or less.
[0226] Industrial Applicability
[0227] The battery of the present disclosure can be used as, for example, an all-solid-state battery.
[0228] Description of Reference Numerals
[0229] 1000 Cathode Materials
[0230] 100 Solid Electrolyte
[0231] 110 Positive electrode active material
[0232] 120 Coating
[0233] 130 Coated active substances
[0234] 2000 Batteries
[0235] 201 Positive electrode
[0236] 202 electrolyte layer
[0237] 203 Negative electrode
Claims
1. A positive electrode material having: Positive electrode active material, and a coating layer covering the positive electrode active material, The coating layer contains oxygen and lithium, The positive electrode active material and the coating layer constitute a coated active material. In the surface layer of the coated active material, a ratio of lithium content to oxygen content (Li / O) is 0.13 or more and 0.26 or less in terms of atomic ratio. When the thickness of the coating layer exceeds the penetration depth of the soft X-ray or electron beam used in the composition analysis, the coating layer is regarded as the surface portion of the coated active material. When the thickness of the coating layer is less than the penetration depth of the soft X-ray or electron beam used in the composition analysis, a portion of the positive electrode active material and the coating layer are contained in the surface portion of the coated active material. 2 . The positive electrode material according to claim 1 , wherein the coating layer contains an alkali metal salt. The positive electrode material according to claim 1 or 2, further comprising a solid electrolyte.
4. The positive electrode material according to claim 3, wherein the solid electrolyte is represented by the following composition formula (1): Li α M β X γ Formula (1) in, α, β and γ are each independently greater than 0, M contains at least one element selected from metal elements and metalloid elements other than Li, X contains at least one selected from F, Cl, Br and I. The positive electrode material according to claim 4 , wherein M contains yttrium. 6 . The positive electrode material according to claim 4 , satisfying 2.5≤α≤3, 1≤β≤1.1 and γ=6. 7 . The positive electrode material according to claim 4 , wherein X contains at least one selected from Cl and Br. 8 . The positive electrode material according to claim 1 , wherein the coating layer contains a lithium niobate-based compound. 9 . The positive electrode material according to claim 1 , wherein the positive electrode active material contains Li and at least one element selected from the group consisting of Mn, Co, Ni and Al.
10. A battery having: A positive electrode comprising the positive electrode material according to any one of claims 1 to 9, Negative electrode, and An electrolyte layer is disposed between the positive electrode and the negative electrode.
11. The battery according to claim 10, The positive electrode material further comprises a solid electrolyte, The electrolyte layer includes a solid electrolyte having the same composition as that of the solid electrolyte contained in the positive electrode material.
12. The battery according to claim 10 or 11, The positive electrode material further comprises a solid electrolyte, The electrolyte layer includes a halide solid electrolyte having a composition different from that of the solid electrolyte included in the positive electrode material. 13 . The battery according to claim 10 , wherein the electrolyte layer comprises a sulfide solid electrolyte.
Citation Information
Patent Citations
Positive electrode material and battery
WO2019135322A1
All-solid lithium ion secondary battery
US20160079597A1
Solid electrolyte material including sulfide layer and oxide layer, and battery including the solid electrolyte material
US20180316057A1